The impact of submarine copper mine tailing disposal from the 1970s on Repparfjorden, northern Norway. Issue 1 (15th July 2017) - Sternal, Beata; Junttila, Juho; Skirbekk, Kari; Forwick, Matthias; Carroll, JoLynn; Pedersen, Kristine Bondo
Abstract: We investigate the state of sedimentological environment and contaminant status of Repparfjorden (N Norway) impacted by submarine disposal of mine tailings during the 1970s using sedimentological and geochemical properties of seventeen sediment cores. The impact of tailings disposal is mainly restricted to the inner fjord where the discharge occurred. Sediment cores retrieved from the inner fjord contain layers of mine tailings up to 9-cm thick, 3–9 cm below the seafloor. Spreading of the tailing-related metal Cu and particles is limited to the inner fjord and to a 2 cm layer in one core from the outer fjord. Two interrelated factors, fjord morphology and sedimentation rate, controlled the distribution of contaminant-laden tailings in the fjord. The mobility of Cu from buried contaminated sediments to the sediment-water interface in the inner fjord indicates that benthic communities have been continuously exposed to elevated Cu concentrations for nearly four decades. Highlights: Past Cu-mine tailings identified in sedimentological and geochemical records Lateral spreading of tailings is mostly restricted to the inner part of the fjord Elevated Cu concentrations in surface sediments in the inner fjord Tailing dispersal controlled by fjord morphology and sedimentation rates Grain-size distribution pattern proves useful tool in marine contamination studies.